PENGARUH EFFICIENCY, SYSTEM AVAILABILITY, FULFILLMENT, DAN PRIVACY TERHADAP LOYALTY MELALUI PERCEIVED VALUEPADA ONLINE TICKETING GARUDA INDONESIA DI SURABAYA - CHANDRA, RYAN SETYONO (Universitas Katolik Widya Mandala Surabaya, 2013)
The growth of online marketing (internet marketing) in Indonesia today is increased. The number of entrepreneurs who want to run their business via the internet is also increased. Low cost internet access in Indonesia encourages the businessman, SME, or cooperation to market their goods and services via the internet. Therefore, E-SQual, which is part of the Service Quality will be more needed. This study aims to empirically examine the influence of Efficiency, System Availability, Fulfillment, and Privacy Of Loyalty Through Perceived Value on Online Ticketing Garuda Indonesia in Surabaya. The object of this study is online ticketingGaruda Indonesia. The sample used in this study amounted to 150 persons. The technique of data analysis using SEM (Structural Equation Modeling). The hypothesis showed that H1: Efficiency influenced on Perceived value, H2: System Availability influenced on Perceived value, H3: Fulfillment influenced on Perceived value, H4: Privacy influenced on Perceived value, H5: Perceived Value influenced on Loyalty, H6: Perceived value into the variable intervening between the influence of Efficiency, System availability, Fulfillment, and Privacy of Loyalty.